2019
DOI: 10.3390/nu11071565
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and Modulation of Bacteria Strains of Akkermansia muciniphila and Faecalibacterium prausnitzii: A Systematic Review

Abstract: Akkermansia muciniphila and Faecalibacterium prausnitzii are highly abundant human gut microbes in healthy individuals, and reduced levels are associated with inflammation and alterations of metabolic processes involved in the development of type 2 diabetes. Dietary factors can influence the abundance of A. muciniphila and F. prausnitzii, but the evidence is not clear. We systematically searched PubMed and Embase to identify clinical trials investigating any dietary intervention in relation to A. muciniphila a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 90 publications
4
93
1
3
Order By: Relevance
“…Therefore, we should conduct a double-blind, randomized, and placebo-controlled pilot study to determine the effects of A. muciniphila on rodents or humans and also to ensure experimental reproducibility. Moreover, although we can form a conclusion about the extraordinary achievement made by A. muciniphila and understand its molecular mechanism in treating obesity, we are unable to quantify the content of A. muciniphila that constitutes an effective dosage (Verhoog et al, 2019). Furthermore, A. muciniphila colonization is extensively different in different human groups; for instance, residents of Southern China had a high rate of A. muciniphila, and over 12 different subtype strains resided in their guts (Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, we should conduct a double-blind, randomized, and placebo-controlled pilot study to determine the effects of A. muciniphila on rodents or humans and also to ensure experimental reproducibility. Moreover, although we can form a conclusion about the extraordinary achievement made by A. muciniphila and understand its molecular mechanism in treating obesity, we are unable to quantify the content of A. muciniphila that constitutes an effective dosage (Verhoog et al, 2019). Furthermore, A. muciniphila colonization is extensively different in different human groups; for instance, residents of Southern China had a high rate of A. muciniphila, and over 12 different subtype strains resided in their guts (Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…As the major environmental factor for intestinal microbiota, dietary intervention, as a healthy lifestyle approach to treating obesity, has been proved to be beneficial for intestine homeostasis and to be strongly associated with a remarkable change in A. muciniphila abundance in the gut (Anhe et al, 2016). Dietary interventions for reducing obesity have been suggested that focus on calorie restriction, energy reduction, or a diet rich in prebiotic fibers, all of which are associated with an increased level of A. muciniphila in the host (Verhoog et al, 2019). For example, clinical trials have shown a significant increase in A. muciniphila in a calorie restriction study of 49 overweight and obese adults (Stenman et al, 2016).…”
Section: Nutritional and Medicinal Approches For Modulation Of Akkermmentioning
confidence: 99%
“…In our experiment, a reduction in Faecalibacterium was also observed: in the same paper of Gao the reduction is found in obese subjects, indicating for the latter a non-positive balance. However, in a very recent paper [29] an increase in Faecalibacterium prausnitzii is believed to be a good indicator of a health condition. In this regard, we must to underline that a large number of study on microbiome in different conditions (such as healthy or ill population, gender differences) do not allow the formulation of unique conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…So far only one species of this order has been described in human faeces: Akkermansia muciniphila . A loss of Akkermansia muciniphila has been associated with metabolic diseases and the abundance may be influenced by diet …”
Section: Discussionmentioning
confidence: 99%
“…A loss of Akkermansia muciniphila has been associated with metabolic diseases and the abundance may be influenced by diet. 68 Changes in microbiome composition in cirrhosis impact intestinal barrier function and lead to intestinal and systemic inflammation due to translocation of bacterial products to the liver and also to the systemic circulation. This concept of a crosstalk between gut, liver and immune system -the so called gut-liver axis-is widely implicated in the pathogenesis of liver disease and a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%